Efforts to Strengthen Digital Talent to Improve the Quality of Human Resources Towards A Golden Indonesia 2045 - Oktoviano, Marinco; Hadiningrat, K.P. Suharyono S. (Yayasan Inspirasi Merah Putih Indonesia, 2025)
This article discusses efforts to strengthen digital talent in Indonesia as a strategic step towards the vision of a Golden Indonesia 2045. The background of the problem includes the challenges faced by Indonesia in utilizing the demographic bonus, where the competence of human resources (HR) must be relevant to the needs of the industry in the era of technological disruption. The purpose of this research is to analyze the policies and initiatives that have been carried out by the government as well as the role of the private sector in the development of digital talent. The discussion included various initiatives such as the Digital Talent Scholarship (DTS) program and the Merdeka Campus policy which aims to improve technical and non-technical skills. The results show that despite progress, there is still a competency gap between higher education graduates and industrial needs, as well as infrastructure challenges that hinder access to technology in disadvantaged areas. The conclusion of this article emphasizes the importance of collaboration between the government, the private sector, and academia in creating an ecosystem that supports the development of digital talent. An integrated policy is needed that harmonizes training and education programs to ensure that Indonesian human resources are ready to compete in the global arena. With this holistic approach, Indonesia can make the most of its digital potential and achieve sustainable development goals towards 2045